Contribution of the International Tribunal For The Law Of The Sea To Strengthening The Marine Environment Protection System - Alobaedi, Omar (Journal of Legal Sciences, 2025)
The United Nations Convention on the Law of the Sea, which was concluded on December 10, 1982, guaranteed cooperation between states in all matters related to the seas. It established a legal system for the seas and oceans that facilitates international communications and encourages the use of the seas and oceans for peaceful purposes and the use of their resources in a manner characterized by fairness and justice. Protecting and preserving the marine environment and preserving its living resources, taking into account the sovereignty of all States, and whereas States Parties bear in mind that achieving these goals will contribute to achieving a just and equitable international economic system that takes into account the interests and needs of all humanity, in particular the interests and needs of developing States, whether coastal or landlocked, When any maritime disputes arise between the states party to the Convention, these states may resort to peaceful means of settling disputes or resort to the courts stipulated in the Convention to resolve maritime disputes.The International Tribunal for the Law of the Sea plays a prominent role in settling international maritime disputes. It is an international judicial body specialized in deciding issues related to the law of the sea, whether it is a matter of interpreting or applying the United Nations Convention on the Law of the Sea of ​​1982, or it is a matter of interpreting or applying an international treaty or agreement. Relevant to the purposes of the Law of the Sea Convention after the parties to that treaty or agreement agreed to refer it to the court. The court received (33) cases in which it decided, including those related to the immediate release of ships and their crew, or related to precautionary measures, or the settlement of maritime borders, or anything related to Protecting the marine environment.